FRI0507 In Adults with Juvenile Onset Dermatomyositis, Visceral Adipose Tissue is Increased Compared with Controls, And is Associated with Serum Lipids. (9th June 2015) - Witczak, B.N.; Godang, K.; Schwartz, T.; Flatø, B.; Bollerslev, J.; Sjaastad, I.; Sanner, H.
Abstract : Background: Autoimmune rheumatic diseases are associated with accelerated atherosclerosis and increased frequency of cardiovascular disease (CVD). An atherogenic lipid profile, characterized by increased triglycerides (TG) and low high density lipoprotein (HDL) has been found in juvenile dermatomyositis (JDM) patients. Evidence supports that visceral adipose tissue (VAT) is a source of inflammation and promotor of atherosclerosis. Assessment of VAT could be important to predict cardiovascular risk. Objectives: To investigate VAT in JDM patients compared with age- and sex-matched controls, and explore the association between VAT and medication, disease activity and damage, pro-inflammatory cytokines and lipids. Methods: Thirty-five adult patients with juvenile onset dermatomyositis, were clinically examined median 24.7 years (7-38) after disease onset and compared with 35 age- and sex-matched controls from the general population. VAT (g) was quantified using a total body dual-energy X-ray absorptiometry (DXA) scan. The pro-inflammatory cytokines MCP-1 and eotaxin were quantified by Luminex technology and lipids were measured (mmol/l) in serum drawn at follow-up. Inactive disease was measured by the PRINTO criteria, disease activity by disease activity score (DAS) and disease damage by myositis damage index (MDI). Results: In JDM patients, mean age was 32.4 (10.4) years and 18/35 (51.4%) were female; 18/35 (51.4%) had inactive disease. Cumulative prednisolone dose was median 9.0 g (IQR 0.9-18.7). Only 4/35 (11.4%) of the patients were on prednisolone and/or disease-modifying antirheumatic drugs at follow-up. VAT was significantly higher in JDM patients compared with controls (median 728 g (IQR 193-1183) vs 232 g (IQR 72-751), p=0.021), despite equal body mass index (BMI) (24.4 vs 24.0 kg/m 2 ). No difference in VAT was found between patients with active and inactive disease. Although 26% of patients had lipodystrophy, no difference in VAT was found between patients with and without lipodystrophy. JDM patients had lower TC (4.3 vs 4.8 mmol/l, p=0.049), HDL (1.1 vs 1.4 mmol/l, p<0.001) and LDL (2.3 vs 2.9 mmol/l, p=0.007) compared with controls. TG were higher in JDM patients (1.9 vs 1.1 mmol/l, p=0.022). MCP-1 and eotaxin were higher in JDM patients compared with controls (41.7 vs 27.0 pg/ml, p=0.001 and 184.3 vs 121.6 pg/ml, p=0.009, respectively). In JDM patients, correlation was found between VAT and HDL (rsp -0.616, p<0.001), and TG (rsp 0.695, p<0.001).These correlations were also found in controls (rsp -0, 599, p=0.001 and rsp 0.406, p=0.032, respectively). No correlation was found between VAT and use of medication at follow-up or cumulative prednisolone dose, DAS, or MDI. MCP-1, but not eotaxin, correlated with VAT in JDM patients (rsp 0.377, p=0.037). Conclusions: Patients with JDM had more than three times higher VAT compared with age- and sex- matched controls, despite equal BMI. However, there was no difference in VAT between active and inactive JDM patients. JDM patients also had more atherogenic lipid profile than controls. Disclosure of Interest: None declared